Evaluation of hibergene loop-mediated isothermal amplification assay for detection of group B streptococcus in recto-vaginal swabs: a prospective diagnostic accuracy study. (October 2018) - Curry, A.; Bookless, G.; Donaldson, K.; Knowles, S.J.
Abstract: Objectives: To prospectively evaluate HiberGene's loop-mediated isothermal amplification (LAMP) assay for detection of group B streptococcus (GBS) in maternal recto-vaginal swabs and compare it with enrichment culture. Methods: Following ethical approval and informed written consent, two low vaginal and rectal swabs were obtained from 400 pregnant women. One swab was tested for GBS using the rapid LAMP assay (index test), the second swab was tested using enrichment culture (reference standard). Antimicrobial susceptibility testing was performed according to EUCAST guidelines. Results: There were 376 concordant results, 20 discordant and four invalid LAMP results. Among discordant results, six were LAMP negative/culture positive and 14 were LAMP positive/culture negative. The sensitivity was 92.2%, specificity 95.6%, positive predictive value 83.5% and negative predictive value 98.1%. The prevalence of GBS carriage was 19.25% (77/400). Forty-eight of 77 GBS-positive women were colonized vaginally (62.3%) and 70 were colonized rectally (90.9%). Erythromycin resistance was 22.4% (17/76) and clindamycin resistance was 17.1% (13/76). Conclusions: The LAMP assay is a rapid and simple test with results available in approximately 1 h compared with 48 h for culture. The test has good sensitivity and specificity compared with enrichment culture. This test can be used for rapid antenatal GBS screening.